The strategic communication of ministry of health in the kingdom of Saudi Arabia during the COVID-19 pandemic - Alturki, Turki (Kansas State University, 2021)
The human and social toll of the coronavirus disease 2019 (COVID-19) pandemic has already spurred several major public health “lessons learned,” and the theme of effective and responsible scientific communication is among them. The Ministry of Health (MOH) in Saudi Arabia used Twitter as a fundamental tool to communicate with the public. This study examined the Twitter response strategies selected by MOH, through the lens of situational crisis communication theory, by using a qualitative content analysis of tweets from the MOH official Twitter account.
Keywords: COVID-19; Strategic communication; Crisis communication